Global study of long term heart rhythm synchronization in groups - Nachum Plonka; Mike Atkinson; Rollin McCraty; Germaine Cornelissen; A. Chase Turner; Minvydas Ragulskis; Alfonsas Vainoras (Scientific Reports)
Abstract Heart rhythm measurements over time reflect important elements of Autonomic Nervous System dynamics. Synchronization among the heart rhythms of multiple participants has been observed, but this study uses the first global dataset collected that measures synchronization at several locations across the globe continuously for multiple weeks. For 15 days, 104 participants located in California (USA), Lithuania, Saudi Arabia, New Zealand, and England underwent continuous ambulatory heart rhythm monitoring. They were not instructed to perform tasks together. Significant long-term correlations were observed across participants within the same region, for just the groups in Saudi Arabia and New Zealand. This is surprising, given that each participant has an individualized life and distinct heart rate. In a different analysis using population-mean cosinor, only in these two locations was a significant circaseptan (about 7-day) rhythm observed. It appears that weekly rhythms in these groups partially contribute to correlations, in addition to long-term movements. A hypothesis with supporting evidence is proposed to explain this, that participants in these groups were socially closer than in the other groups. It would then appear that heart rhythms synchronize over the long term due to social connectedness, even when they are not physically near each other or performing tasks together.